STATUS PENGELOLAAN LINGKUNGAN PERTANIAN KOTA DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Agussalim Simanjuntak; Tengku Nurhidayah; Nofrizal Nofrizal (Jurnal Ilmu Lingkungan, 2015)
Urban agricultural expanding on empty farm near in settlement and society activityplace which utilized to fulfill the urban society food. Usage of chicken dirt manure,chemical manure, pesticide must be doing to have a high vegetables production so thatadvantage was reached. Usage an abundant of manure and pesticide can contaminatethe environment. The experimental has done to analyzed management of urbanagricultural environment, and impact of urban agricultural on environmental biofisic.Management of urban agricultural environmet was doing by farmers got by asking withquesioner in random sampling, analyzed water and soil to find biofisic aspect with apurposive sampling on three point of water sample and two point of soil sample. Thequality of water sample compared to Peraturan Pemerintah Nomor 82 Tahun 2001,while two point of soil sample was comparing. The result of this study shown that: thefarmer never use an urban biomass, manure composit and vegetation pesticide; usageof chemical manure and pesticide increasing nitrat (NO3) contains on agricultural landwater haved passed away the boundary sill and a very low of pH value.